Reconceptualization of the Scope of Parties in Disputes Handled by the Financial Services Sector Alternative Dispute Resolution Institution (LAPS SJK) - Theresia Gabriella; Rianda Dirkareshza (Lambung Mangkurat Law Journal, 2025)
The rapid growth of the financial services sector in Indonesia has increased the potential for disputes between consumers and financial service providers (PUJK), thereby necessitating an effective dispute resolution mechanism. In response, the Financial Services Authority (OJK) established the Financial Services Sector Alternative Dispute Resolution Institution (LAPS SJK) through Regulation No. 61/POJK.07/2020 as an enhancement of the previous regulation. LAPS SJK is the result of a merger of six sectoral dispute resolution institutions to simplify the resolution process across various financial service sectors. However, in its implementation, there has been a regulatory disharmony concerning the definition and scope of parties eligible to access LAPS SJK services. Law No. 4 of 2023 limits consumers to individuals, while POJK 61/2020 expands the definition to include users of PUJK services, and LAPS SJK Regulation No. 1 refers to "legal subjects," thereby making the scope more inclusive. This inconsistency creates legal uncertainty and potentially hinders access to justice. This research adopts a normative legal approach to analyze the regulatory disharmony and recommends the need for a reconceptualization of the definition of disputing parties. Harmonizing the regulations is expected to improve the effectiveness and inclusiveness of LAPS SJK in resolving disputes and strengthen legal protection in the financial services sector.